Krop, sind og sjæl: erfaringer med en kropsterapi - Hildebrandt, Lise (Tidsskriftet Antropologi, 2019)
The article presents Ma-uri massage as a therapeutical practice, an institution and an experience with the body. The aim of the article is to give examples of non-dualistic experiences with the body. The main point of the article is that Ma-uri massage as a healing activity challenges the Western body/soul dualism and the related definitions of the body and perceptions of reality. The article opens with an account of context and data, followed by a brief description of the Ma-uri Institute and recruitment of potential Ma-uri masseurs. This is followed by descriptions of Ma-uri massage. Leaming techniques and therapeutical processes are presented under the subtopics “Body and Cosmos”, “Perceptions of Person”, and “The Body as a Symbol”. The article ends with proposals for future research within the area.